2009
DOI: 10.1001/archsurg.2009.216
|View full text |Cite
|
Sign up to set email alerts
|

Endolaparoscopic Approach vs Conventional Open Surgery in the Treatment of Obstructing Left-Sided Colon Cancer

Abstract: Self-expanding metal stents serve as a safe and effective bridge to subsequent laparoscopic surgery in patients with obstructing left-sided colon cancer. This endolaparoscopic approach makes a 1-stage operation more feasible, is associated with reduced incidence of stoma creation, and allows patients with malignant large-bowel obstruction to enjoy the full benefit of minimally invasive surgery. Trial Registration clinicaltrials.gov Identifier: NCT00654212.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
3
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(163 citation statements)
references
References 27 publications
(32 reference statements)
9
136
3
15
Order By: Relevance
“…(3) Las dos principales indicaciones para el tratamiento de la obstrucción maligna de colon son la descompresión de la luz intestinal previo a cirugía programada (puente a la cirugía), y paliación en caso de tumores no candidatos a intervención curativa.…”
Section: Indicacionesunclassified
See 1 more Smart Citation
“…(3) Las dos principales indicaciones para el tratamiento de la obstrucción maligna de colon son la descompresión de la luz intestinal previo a cirugía programada (puente a la cirugía), y paliación en caso de tumores no candidatos a intervención curativa.…”
Section: Indicacionesunclassified
“…El carcinoma colorectal puede debutar como obstrucción en un 7-29%, siendo la causa más frecuente de intervención urgente en estos casos ya que dejada a su evolución, la distensión progresiva del intestino progresa desde dolor abdominal con náuseas y vómitos hacia la isquemia intestinal, perforación, sepsis y posterior fallecimiento del paciente. (3) La cirugía urgente debe realizarse respetando los principios oncológicos aunque no se disponga de un diagnostico de certeza prequirúrgico, y la intención debe ser curativa si no hay evidencia de enfermedad a distancia. (1) La Tomografía Computarizada (TC) es la prueba radiológica de elección para localizar la lesión y la morfología de la obstrucción.…”
Section: Introductionunclassified
“…15 This guideline is based on the evidence from eight systematic reviews with meta-analysis comparing preoperative stenting with emergency resection for left-sided colonic malignant obstruction, 11,[36][37][38][39][40][41][42] with assimilated data from up to seven RCTs. [43][44][45][46][47][48][49] Three of those RCTs were closed early due to adverse outcomes in the SEMS group (higher 30-day morbidity related to stent perforation), 43,44 or high anastomotic leak rate in the emergency surgery group. 48 The most recently published meta-analysis found that SEMS as a bridge to surgery (n = 195) compared to emergency surgery (n = 187) had a lower overall morbidity (33.1% vs 53.9%, P = 0.03), a higher successful primary anastomosis rate (67.2% vs 55.1%, P < 0.01), and a lower permanent stoma rate (9% vs 27.4%, P < 0.01); however, there was no statistical difference in post-operative mortality (10.7% vs 12.4%).…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%
“…An at least theoretical approach to circumvent the emergency operation and its complications is the bridging of the obstruction with a stent. It allows after decompression of the left colon and mechanical bowel preparation scheduled surgery of the patient with a high rate of primary anastomoses [11][12][13] . In this context, I read the recent systematic review and meta-analysis published by Tan et al [14] with great interest and I strongly recommend it to readers.…”
Section: Commentary On Hot Topicsmentioning
confidence: 99%